Holistic Technological Guideline of Nuclear Power Plant Inception of Bangladesh and Developing Countries (Global Journals of Research in Engineering, 2013)
Energy performs a cardinal role in strategies of preferment for the developing countries. Traditional energy source reliance is a prima challenge for ameliorating the performance of their energy suppliers to benefit energy consumers. Hydrocarbons are already used a great deal as an energy source and they also harshly criticized because oil and gas are expensive. Consequently some developing countries are trying to cope up the challenge by considering the nuclear energy in their power production. Nuclear energy is the only nongreenhouse gas-emitting reliable and safe base load power source that can effectively replace fossil fuels and satisfy growing demands for energy. The average cost of producing nuclear energy comparing with coal and gas is quite low but sometimes takes cumbersome steps to establish the nuclear power plant. So this paper emphasizes on the supersede of conventional energy with nuclear power and the roadmap for the developing countries like Bangladesh to establish the nuclear power plant.
Keywords: bangladesh; developing country; expenditure of nuclear power plant; nuclear power plant; site selection